Haemangioma Family Burden: Creation of a Specific Questionnaire - Boccara, O; Méni, C; Léauté-Labreze, C; Bodemer, C; Voisard, J; Dufresne, H; Brauchoux, S; Taieb, C (Acta dermato-venereologica, 2015)
To develop and validate a specific questionnaire to assess burden on families of children with infantile haemangioma (IH): the Haemangioma Family Burden questionnaire (HFB). Items were generated from a literature review and a verbatim report from parents. Subsequently, a study was implemented at the Necker Hospital and the Pellegrin Children's Hospital for psychometric analysis. The HFB was refined via item reduction according to inter-question correlations, consensus among experts and exploratory factor analysis. A 20-item questionnaire, grouped into 5 dimensions, was obtained. Construct validity was demonstrated and HFB showed good internal coherence (Cronbach's α: 0.93). The HFB was significantly correlated with the mental dimension of the Short-Form-12 (r = -0.75), and the Psychological General Well-Being Index (r = -0.61). HFB scores differed significantly according to the size and localization of the IH. A validated tool for assessing the burden on families of children with IH is now available.